Rainfall Analysis of Drainage Cross-Sectional Capacity with Comparison of Mononobe Method and Van Breen Method on The Road Asrama Sei Kambing C-Ii (Case Study) - Elly Ria (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
The intensity of rainfall is one of the factors causing inundation in an area which is one of the drainage problems in the city of Medan which is increasingly feared in recent years, population growth in the city of Medan is increasingly rapid and the need for land that was originally green is now becoming a denser residential area and more and more road paving which causes rainwater cannot absorb into the ground. In addition to flooding factors, watershed conditions that often experience erosion make river silting which results in reduced flow carrying capacity so that the increase in discharge is greater so that overflow occurs. The purpose of this rainfall analysis is to find out what problems make puddles not fully drain water when the rain discharge is high and to find out how much cross-sectional capacity is suitable to be used in accommodating flood discharge in drainage at the research site. The research method calculates rainfall intensity by comparing the Mononobe method and Van Breen method by analyzing the plan discharge to determine the feasibility of cross-sectional capacity by analyzing the planned flood discharge, where the results of the analysis of the 2-year period of channel discharge capacity (Qs) = 262.622 m3⁄sec so that the calculation results that the value of the channel discharge capacity is smaller than the plan flood discharge value is greater, so that the capacity proves that the drainage canal is not able to accommodate the flow of water which results in flooding.